The Ukrainian crisis and European security : implications for the United States and U.S. Army - Larrabee, F. Stephen; Wilson, Peter A., 1943-; Gordon, John, 1956- (Rand Corporation, 2015)
Vladimir Putin's decision to annex Crimea and attempt to destabilize eastern Ukraine have sparked widespread concern among Western policymakers that Russia has embarked on a confrontational national security policy that could have far-reaching implications for Russia's relations with the United States and for European stability. The annexation of Crimea challenges two basic assumptions underlying U.S. policy toward Europe in the post-Cold War era: (1) that Europe is essentially stable and secure, thereby freeing the United States to focus greater attention on other areas, particularly Asia and the Middle East, and (2) that Russia had become more of a partner than an adversary. The annexation of Crimea and attempt to destabilize eastern Ukraine suggests that both these assumptions need to be revisited because Russia can hardly be viewed as a partner. The requirement that NATO may now have to build a much more robust deterrence and defense posture in Eastern Europe would require the Army and the Air Force to revisit their planning assumptions that have minimized U.S. military commitments to the region since the end of the Cold War.